Black Self-Employed Women in the Twenty-First Century: A Critical Approach - Knight, Mélanie (Canadian Woman Studies/Les cahiers de la femme, 2004)

For us by us (FUBU): The politicized space of Black women's entrepreneurship in Canada - Knight, Melanie (Southern Journal of Canadian Studies, 2012)

Race-ing, Classing and Gendering Racialized Women's Participation in Entrepreneurship - Knight, Melanie (Gender, Work & Organization, 2016)

“It’s Not Just about Work and Living Conditions”: The Underestimation of the COVID-19 Pandemic for Black Canadian Women - Knight, Melanie; Ferguson, Renée Nichole; Reece, Rai (Social Sciences, 2021)
The COVID-19 pandemic has increasingly been deﬁned as the shecession for its disproportionate debilitating impact on women. Despite this gendered analysis, a number of health activists have called on governments to account for the experiences of Black communities as they are disproportionately suffering the effects of this pandemic. In the media’s address of the impact of the pandemic, we ask, what experiences are represented in news stories and are Black women present in these representations. Performing a content analysis of 108 news articles, a reading of media discourses through a racial lens reveals a homogenization of women’s experiences and an absence of the Black experience. In the small number of news stories that do focus on Black women, we see that the health disparities are not simply the result of precarious work and living conditions, but also the struggle against anti-Black racism on multiple fronts. In critiquing, however, we also bring forth the small number of news stories on the Black experience that speak to the desire and hope that can thrive outside of white supremacist structures.